Extension of the VIKOR method in a decomposed fuzzy environment for addressing inconsistencies in decision-making - Arslan, Ozlem; Cebi, Selcuk (SPRINGER INDIA, 2026)
This paper introduces a novel extension of the VIseKriterijumska Optimizacija I Kompromisno Resenje extended with Decomposed Fuzzy Sets, denoted as Decomposed Fuzzy VIKOR, which aims to address the challenges of inconsistent responses and indecision among decision-makers. As a recent contribution to fuzzy set extensions, Decomposed Fuzzy Set differ from other extensions by employing bidirectional questioning. The aim of bidirectional questioning is to allow decision-makers to provide responses by posing questions that are equivalent in meaning but represent two opposing perspectives: functional (optimistic) and dysfunctional (pessimistic). In this study, six criteria obtained from a comprehensive literature review are considered, and the Decomposed Fuzzy VIseKriterijumska Optimizacija I Kompromisno Resenje method is applied to a cold food supply chain to identify the most suitable alternatives based these criteria. The results are compared with those obtained using the Intuitionistic Fuzzy VIseKriterijumska Optimizacija I Kompromisno Resenje method, revealing the impact of different scenarios on optimal alternatives. The paper concludes by emphasizing the significance of integrating various multi-criteria decision-making methods with Decomposed Fuzzy Set for real-life problem-solving.
Keywords: Cold food supply chain; Decision-making; Decomposed fuzzy sets; Intuitionistic fuzzy sets; Multi-criteria decision making; VIKOR; Operations Research & Management Science